2022
DOI: 10.1021/acsami.2c16025
|View full text |Cite
|
Sign up to set email alerts
|

Acetylated Distarch Phosphate-Mediated Tough and Conductive Hydrogel for Antibacterial Wearable Sensors

Abstract: Conductive, stretchable, and flexible hydrogel wearable sensors have attracted extensive attention in the fields of artificial intelligence and electronic equipment. However, it is an enormous challenge to fabricate conductive hydrogel sensors with biocompatibility, antibacterial properties, and toughness. Here, a highly conductive hydrogel with excellent toughness, good biocompatibility, and strong antibacterial properties was prepared by incorporating acetylated distarch phosphate (ADSP) into poly(vinyl alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Moreover, in vivo antibacterial experiments demonstrated that the hydrogel could effectively kill S. aureus in the wound (>97.1%). In addition to ionic liquids, there are some significant developments in antibacterial hydrogel based on novel synthetic materials such as N -halamine compounds [ 137 ], quaternary ammonium compounds [ 138 ], imidazole derivatives [ 139 ], biguanides [ 140 ], phenols [ 141 ], nitriles [ 116 ] et al. For example, positively charged quaternary ammonium salts can bind to negatively charged bacterial cell walls, then disrupt the bacterial structure.…”
Section: Antibacterial Hydrogel Wound Dressingsmentioning
confidence: 99%
“…Moreover, in vivo antibacterial experiments demonstrated that the hydrogel could effectively kill S. aureus in the wound (>97.1%). In addition to ionic liquids, there are some significant developments in antibacterial hydrogel based on novel synthetic materials such as N -halamine compounds [ 137 ], quaternary ammonium compounds [ 138 ], imidazole derivatives [ 139 ], biguanides [ 140 ], phenols [ 141 ], nitriles [ 116 ] et al. For example, positively charged quaternary ammonium salts can bind to negatively charged bacterial cell walls, then disrupt the bacterial structure.…”
Section: Antibacterial Hydrogel Wound Dressingsmentioning
confidence: 99%
“…Furthermore, they are safe for humans and animals. In particular, their excellent heat resistance renders them widely useful in the field of plastic antibacterial modification. Recently, polypentamethylene guanidine hydrochloride (PPMG), which is synthesized from biobased pentamethylene diamine, has attracted significant attention as a green antibacterial agent. , However, similar to the use of ordinary guanidine salts, the long-term use of this antibacterial agent corrodes the processing equipment, specifically at high temperatures . During the normal corrosion process, a passivation film is formed on the metal surface, which changes the state of the metal from active to passive, thus improving its corrosion resistance. , When active halogen ions come into contact with metal surfaces due to their small size, they diffuse easily into the metal passivation films and increase the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The overlap of wearable healthcare applications and flexible electronic engineering is guiding the development direction of functional soft materials , and device design integration. , Recently, hydrogel-based wearable sensors with high hydration, tunable functionality, and high sensitivity have shone in fields such as medical devices, human–machine interfaces, and flexible electrodes. For example, Fu et al developed a super-stretchable conductive hydrogel based on triple crosslinking for sensitive monitoring of human physiological motions . Nevertheless, due to the lack of adhesion properties, the conventional hydrogel-based strain sensor required additional assistance to achieve close contact between the sensor and the substrate during usage, which largely impair the accuracy and durability of signal detection. Meanwhile, these hydrogels were easily damaged during the complex and continuous movement of the human body, which limited their application especially in human health care monitoring.…”
Section: Introductionmentioning
confidence: 99%